Toxin - Cook, Robin (Thorndike, Me. : G.K. Hall, 1998)
On a special night out, a father/son outing for burgers and fries turns into tragedy as the boy becomes fatally ill and dies within hours as a result of E. coli poisoning. Taking a leave from his practice, Dr. Kim Regis is determined to find out who is responsible for his son's death. Not only does he hit a brick wall of silence, he soon meets with violence as thugs attempt to stifle his inquiry. With his trademark pulse-pounding flair, Robin Cook delivers a cutting-edge thriller, borrowing from today's fears and tomorrow's technology.
"G.K. Hall large print core series."
77746
Keywords: Large type books; Detective and mystery stories